PMO-061 An evaluation of the impact of a multidisciplinary nutrition support team on the provision of parenteral nutrition (PN) in an NHS Foundation Trust Hospital. (28th May 2012) - El-Alem, L; May, C J; Ali, C; Livingstone, C; Sadler, G J
Abstract : Introduction: In June 2010 NCEPOD released its report: A Mixed Bag. 1 This instructed hospitals providing PN to encourage active input from a multidisciplinary NST. The process involved in providing PN to patients involves complex decision-making, and it is life-saving for some. However, when given inappropriately or without careful monitoring, there can be serious metabolic and physiological consequences. This audit examined the impact a NST has on the appropriate prescribing of PN. Methods: The study included patients who received PN at the Royal Surrey County Hospital over the period 1 June 2010 to 1 June 2011. Data were collected in line with the NCEPOD report, including when and by whom PN was started, indication for use and number of days fed. Results: During the study period, 171 patients were referred for PN. In 61% of cases the opinion of the NST was requested prior to the commencement of PN (Group A). In the remaining 39% of cases (Group B), PN was initiated without NST involvement, with the NST review occurring subsequently. On review, the NST considered PN to be an inappropriate means of nutritional support in 25.7% of the patients in Group A, and it was therefore not provided. Of these patients, 81% were successfully established onto either oral or enteral feeding, and a further 8% died shortly after referral. The remaining 11% later received PN due to loss of enteral access or further post-operative complications. There was no survival disadvantage in this group. Of the patients in Group B, 33% were commenced on PN over a weekend. Of these 38% received PN for <5 days and 19% for <3 days. Following assessment, the NST, believed that 14% of the patients in group B were started on PN when an alternative means of providing nutritional support would have been more suitable at the time of initiation. Conclusion: Prescribing of PN continues to occur both out of hours and without consultation with a dedicated NST. Our data demonstrates that timely involvement of the NST in feeding decisions can avert inappropriate initiation of PN in a significant proportion of cases, which has clinical and cost-saving implications. We therefore strongly recommend that clinicians should utilise the expertise of a multidisciplinary NST at the earliest opportunity in complex feeding scenarios. Competing interests: None declared. Reference: 1. NCEPOD . A Mixed Bag: An Enquiry Into The Care Of Hospital Patients Requiring Parenteral Nutrition, 2010.